A Multimodality Navigation System for Endoscopic Fetal Surgery: A Phantom Case Study for Congenital Diaphragmatic Hernia. (February 2019) - Elangovan, Hariprashanth; Yao, Wei; Nicolaides, Kypros
This article presents a multi-modality tracking and navigation system achieved by merging optical tracking and ultrasound imaging into a novel navigation software to help in surgical pre-planning and real-time target setting and guidance. Fetal surgeries require extensive experience in coordination of hand-eye-ultrasound-surgical equipment, knowledge, and precise assessment of relative anatomy. While there are navigation systems available for similar constrained working spaces in arthroscopic and cardiovascular procedures, fetal minimally invasive surgery does not yet have a dedicated navigation platform capable of supporting robotic instruments that can be adapted to the set of unique procedures. This article discusses the testing of the novel multi-modality navigation system in a phantom environment developed for this purpose. The outcomes suggest that the subjects demonstrated an increase in average reaching accuracy by about 60% and an overall reduction in time taken by 33.6%. They also showed higher levels of confidence in reaching the targets, which was visualised from the pattern of trajectory of movements during the procedure. To evaluate the navigation system, a phantom surgical environment was found necessary. Therefore, the article also discusses the details of the development of a fetal phantom environment for congenital diaphragmatic hernia for surgical testing, evaluation, and training. A surgical procedure was conducted on the phantom using the proposed tracking navigation system and using only ultrasound.